Live Related versus Cadaveric Limbal Allograft in Limbal Stem Cell Deficiency. (June 2015) - Titiyal, Jeewan S.; Sharma, Namrata; Agarwal, Ashish K.; Prakash, Gaurav; Tandon, Radhika; Vajpayee, Rasik
Abstract Aim: To compare outcomes of live related limbal allograft (Lr-CLAL) versus cadaveric keratolimbal allograft (KLAL) in limbal stem cell deficiency (LSCD) secondary to ocular burns. Methods: Twenty patients with stage IIb LSCD were randomized so that cases underwent either Lr-CLAL or KLAL. Fibrovascular pannus was removed and superficial keratectomy done on the recipient bed. Limbal lenticule of 2–3 clock hours' length was harvested from the donor, which was placed over the host bed and sutured followed by bandage contact lens application. Parameters assessed were uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), conjunctivalization, corneal neovascularization, epithelial defects, corneal clarity, Schirmer's test, tear film breakup time (tBUT), and ultrasonic pachymetry. Results: At 6 months follow-up, the Lr-CLAL group had a higher gain in vision (p = 0.029), decrease in conjunctivalization (p = 0.009), and increase in Schirmer's values (p = 0.009). Conclusion: Lr-CLAL seems to have better result in terms of vision gain and ocular surface restoration.